A versatile split Hopkinson pressure bar using electromagnetic loading. (June 2018) - Nie, Hailiang; Suo, Tao; Wu, Beibei; Li, Yulong; Zhao, Han
Highlights: Split Hopkinson compressive or tensile bar test with an electromagnetic stress pulse generator. Incident stress pulse directly generated by Lorentz magnetic force due to a sudden discharge in an LC circuit. Easy control of the amplitude and the duration of generated stress pulses by the capacitance and the charging voltage of the LC circuit. Compressive or tensile stress pulse generation using the same electromagnetic stress pulse generator. Accurate trigger control of the stress pulse within a few microseconds permitting for a synchronization of multiple pulses. Abstract: This paper presents a novel electromagnetic split Hopkinson pressure bar (ESHPB), which employs the electromagnetic energy conversion technique of LC circuit to generate directly the incident stress pulse. Such a versatile technique can generate easily compressive as well as tensile incident pulses. The duration and amplitude of the incident pulse could be controlled by adjusting the capacitance and charging voltage in the LC circuit. Therefore, compressive or tensile high strain-rate tests can easily be performed using the present apparatus by simply choosing the compression bars or tension bars. The primitive shape of generated stress pulse is a half-sine function, which is well suited for testing brittle materials and soft rubber-like materials in order to reach a rather constant strain rate. Meanwhile, for the tests of metals, a pulse shaper can be used to reach a rather classical trapezoidal pulse similar to that of the classical pressure bar tests. Furthermore, it is also possible to modify the stress pulse by shaping the discharge current using a specially designed active coil array and a sequential switch. Finally, a number of different materials were tested in compression and tension using this electromagnetic split Hopkinson bar system. The same materials were also tested using the traditional split Hopkinson bars. It turns out that the results obtained by the present device are consistent with those by the traditional split Hopkinson bars. Compared with traditional pulse generation techniques by the impact of a projectile or by a sudden release of a pre-stressed section, the proposed electromagnetic energy conversion technique can be accurately triggered within several microseconds. It is, therefore, a good candidate to supply the symmetrical and synchronous loads in bidirectional or biaxial split Hopkinson bar systems in the future.